Broad-range survey of vector-borne pathogens and tick host identification of Ixodes ricinus from Southern Czech Republic. Issue 11 (3rd October 2017) - Honig, Vaclav; Carolan, Heather E.; Vavruskova, Zuzana; Massire, Christian; Mosel, Michael R.; Crowder, Christopher D.; Rounds, Megan A.; Ecker, David J.; Ruzek, Daniel; Grubhoffer, Libor; Luft, Benjamin J.; Eshoo, Mark W.
Abstract: Ixodes ricinus ticks are vectors of numerous human and animal pathogens. They are host generalists able to feed on more than 300 vertebrate species. The prevalence of tick-borne pathogens is influenced by host–vector–pathogen interactions that results in spatial distribution of infection risk. Broad-range polymerase chain reaction electrospray ionization mass spectrometry (PCR/ESI-MS) was used to analyze 435 I. ricinus nymphs from four localities in the south of the Czech Republic for the species identification of tick-borne pathogens. Borrelia burgdorferi sensu lato spirochetes were the most common pathogen detected in the ticks; 21% of ticks were positive for a single genospecies and 2% were co-infected with two genospecies. Other tick-borne pathogens detected included Rickettsia helvetica (3.9%), R. monacensis (0.2%), Anaplasma phagocytophilum (2.8%), Babesia venatorum (0.9%), and Ba. microti (0.5%). The vertebrate host of the ticks was determined using PCR followed by reverse line blot hybridization from the tick's blood-meal remnants. The host was identified for 61% of ticks. DNA of two hosts was detected in 16% of samples with successful host identification. The majority of ticks had fed on artiodactyls (50.7%) followed by rodents (28.6%) and birds (7.8%). Other host species were wild boar, deer, squirrels, field mice and voles. Abstract : Prevalence of multiple human and veterinary pathogens was estimated in host-seeking nymphal Ixodes ricinus ticks, and their previous vertebrate host was determined.